Surface engineering of nanoporous substrate for solid oxide fuel cells with atomic layer-deposited electrolyte - Ji, Sanghoon; Tanveer, Waqas Hassan; Yu, Wonjong; Kang, Sungmin; Cho, Gu Young; Kim, Sung Han; An, Jihwan; Cha, Suk Won (Beilstein Journal of Nanotechnology, 2015)
Solid oxide fuel cells with atomic layer-deposited thin film electrolytes supported on anodic aluminum oxide (AAO) are electrochemically characterized with varying thickness of bottom electrode catalyst (BEC); BECs which are 0.5 and 4 times thicker than the size of AAO pores are tested. The thicker BEC ensures far more active mass transport on the BEC side and resultantly the thicker BEC cell generates ≈11 times higher peak power density than the thinner BEC cell at 500 °C.
Keywords: anodic aluminum oxide; atomic layer deposition; bottom electrode catalyst; mass transport; solid oxide fuel cell